Strategi Pemasaran Digital Dalam Peningkatan Penerimaan Mahasiswa Baru Menggunakan Analisis SWOT - Kristanto, Titus; Hadiansyah, Walid Maulana; Nasrullah, Muhammad; Amalia, Amanda; Anggraini, Erlin Yuli; Firmansyah, Ainurrohman (POLITEKNIK NEGERI JAKARTA, 2020)
One of the tertiary institutions in Surabaya City, East Java Province, is experiencing a decline in new students from the target that has been determined in previous years. The analysis conducted by tertiary institutions uses a SWOT analysis approach, by looking at the conditions experienced both from internal and external aspects. In addition, tertiary institutions also look at the aspects of opportunities and threats that affect new student admissions. In addition to looking at the four aspects, universities see the supporting factor in the admission of new students from the variable